Reactive Oxygen Species: Beyond Their Reactive Behavior - Tauffenberger, Arnaud (Neurochem Res, 2021)
Cellular homeostasis plays a critical role in how an organism will develop and age. Disruption of this fragile equilibrium is often associated with health degradation and ultimately, death. Reactive oxygen species (ROS) have been closely associated with health decline and neurological disorders, such as Alzheimer’s disease or Parkinson’s disease. ROS were first identified as by-products of the cellular activity, mainly mitochondrial respiration, and their high reactivity is linked to a disruption of macromolecules such as proteins, lipids and DNA. More recent research suggests more complex function of ROS, reaching far beyond the cellular dysfunction. ROS are active actors in most of the signaling cascades involved in cell development, proliferation and survival, constituting important second messengers. In the brain, their impact on neurons and astrocytes has been associated with synaptic plasticity and neuron survival. This review provides an overview of ROS function in cell signaling in the context of aging and degeneration in the brain and guarding the fragile balance between health and disease.